2012
DOI: 10.1590/s1415-790x2012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors with alcohol use disorders among adults: a population-based study in southern Brazil

Abstract: OBJECTIVES: The study aimed to describe the prevalence of alcohol use disorders in an adult population from Brazil and its association with demographic, socioeconomic, behavioral variables and health conditions. METHODS: A population-based cross-sectional survey was conducted with adults (20 to 59 years) of a medium-sized city in Southern Brazil with a random sample of 1,720 individuals. Cluster sampling was done in two stages: census tract first and household second. Alcohol use disorders were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
42
0
18

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 33 publications
11
42
0
18
Order By: Relevance
“…Overall, the prevalence of the risk behaviors examined in this study was similar to that reported in other Brazilian studies, and the same was true for the differences found by demographic and health-related variables 42,43,44,45,46,47 .…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the prevalence of the risk behaviors examined in this study was similar to that reported in other Brazilian studies, and the same was true for the differences found by demographic and health-related variables 42,43,44,45,46,47 .…”
Section: Discussionsupporting
confidence: 90%
“…Alcohol-related problems represent an immense economic loss to many communities around the world [11][12][13] . AUDIT was developed by the World Health Organization (WHO) to screen for excessive drinking 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…AUDIT was developed by the World Health Organization (WHO) to screen for excessive drinking 14,15 . AUDIT has been validated in many countries and has showed good levels of sensitivity and specificity for alcohol use disorders [12][13][14][15] . Our study suggests that migraine reduces harmful alcohol consumption and alcohol-related problems in comparison with tension type headache.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations